Factors shaping local people's perception of ecosystem services in the Atacora Chain of Mountains, a biodiversity hotspot in northern Benin - Fidèle Tchossi Moutouama; Samadori Sorotori Honoré Biaou; Boateng Kyereh; Winston Adam Asante; Armand K. Natta (BMC, 2019)
Abstract Background Atacora Chain of Mountains (ACM) is the Benin part of a range of mountains lying from Benin to Ghana through Togo. It provides goods and services to people and is dominated by rural communities with heavy reliance on natural resources. The ACM may be threatened by the increasing resource needs and the possible shift in people's livelihood priorities brought about by challenges and opportunities ushered in by modernization. This study sought to understand local people's perception of the services derived from the ACM and the socio-demographic factors (age, gender, and level of urbanization of the place people live in) accounting for these perceptions. Methods Face to face interviews with 12 focus groups in 3 municipalities were carried out to obtain a list of ecosystem services cited by the participants. At the individual level, 144 people (men, women, young, adult, and old people from either rural or urbanized areas) equally distributed in the 3 municipalities were asked whether they acknowledge each of the services cited by the focus groups. Logistic regressions were then used with generalized linear models (GLM) function in R to analyze the relationships between the probability of acknowledgement of a service by the respondents and their socio-demographic characteristics. Results Local people perceived the ACM as a provider of provisioning, supporting, and cultural services but cited more provisioning services than the others. The factors considered in this study (gender, location, and age) were all predictors of ecosystem services perception in the ACM. Location influenced people's perception of provisioning and supporting services such that respondents from rural municipalities were more likely to perceive provisioning and supporting services. This is because people in rural areas have a heavier reliance on natural resources. Gender was associated with respondents' perception of supporting, provisioning, and cultural services. Women were more likely to perceive provisioning services and less likely supporting and cultural services. People in each category of gender have a perception of ES linked to their livelihood activities. Young people were less likely to perceive supporting services than adults and old people due to their less involvement in farming activities. Conclusions This study showed that gender, location, and age predict local people's perception of ecosystem services in the ACM and livelihood orientation is determinant. The omission of regulation and many of the supporting services questions the future of this mountain chain if its exploitation continues without any awareness and conservation measures.